The body as strategy of power in religious discourse - Vorster, Johannes N. (Neotestamentica, 1997)
The objective of this article is to consider the body as a means through which access may be, gained into a better understanding of a culture and the processes involved in the formation and changes within cultures. Owing to the rhetoricity of the body, the body may function as an agent of change. This point of departure is illustrated by examples from early Christianity and from the official journal of the Dutch Reformed Church during 1991-1995.